DIABETES SELF-CARE EXPERIENCE ON ELDERLY WITHOUT MEDICATION - Niko Dima Kristianingrum; Wiwin Wiarsih; Astuti Yuni Nursasi (Journal of Nursing Science Update (JNSU), 2018)
Increasing of the number of elderly contributes to the increasing of prevalence of chronic degenerative diseases such as diabetes mellitus. Diabetes mellitus requires long-term care through self-care. Theaims of this study to find out the experience of elderly on diabetes self-care. The study used qualitative method of descriptive phenomenology with in-depth interviews on nine participants. Interview results were analyzed using the Colaizzi method. The results of the study identified a variety of self-care diabetes, were regulates food, exercise, and blood sugar checking. Self-care has not been done consistently so it needs diabetes self-care guidelines, diabetes self-care education, and a community health nurse program that can foster elderly with diabetes mellitus.